Implementasi Kebijakan Bahasa Bali Dalam Penggunaan Tanda Bahasa di Ruang Publik - Artawa, Ketut; Sri Satyawati, Made; Widya Purnawati, Ketut; Yendra, Yendra (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
The rapid development of multiculturalism and multilingualism along with the growth of tourism in Bali has greatly contributed to the decline number of Balinese languages speakers. Therefore, in order to empower and promote the sustainable use of the Balinese language and script, the government issued a policy through: Bali Governor Regulation Number 80 of 2018 (Balinese Language Policy). This study discusses the implementation of the Balinese Language Policy in the use of language sign in public spaces, as well-known as Linguistic Landscape (LL). Specifically, the discussion refers to Balinese Language Policy Article 6 paragraph (1) which requires the use of Balinese script above Latin letters in writing names of Hindu places of worship, traditional institutions, inscriptions marking the inauguration of buildings, government institution buildings, private institutions, streets, tourism facilities, and other public facilities. This study conducts qualitative-descriptive method with research procedures, namely an empirical survey of language signs in public spaces, classification of language signs, and analysis of the implementation of Balinese Language Policy on language signs in public spaces. In the analysis of language signs in Balinese LL, signs are classified into ‘public signs’ and ‘personal signs’. Based on the data analysis, it was found that the Balinese Language Policy was implemented effectively in accordance with the policy on public signs. On the contrary, the implementation of the policy on personal signs did not go as effectively as that of the public signs because there were only a small number of people who implemented the policy